2022
DOI: 10.3390/ijerph19063182
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model and Mortality Risk Score during Admission for Ischaemic Stroke with Conservative Treatment

Abstract: Background: Stroke is the second cause of mortality worldwide and the first in women. The aim of this study is to develop a predictive model to estimate the risk of mortality in the admission of patients who have not received reperfusion treatment. Methods: A retrospective cohort study was conducted of a clinical–administrative database, reflecting all cases of non-reperfused ischaemic stroke admitted to Spanish hospitals during the period 2008–2012. A predictive model based on logistic regression was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…In this analytical observational study, we perform an external validation and subsequent recalibration of the coefficients of the original variables from a prior model [11] used to predict the mortality at first admission of patients with non-reperfused ischaemic stroke.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations
“…In this analytical observational study, we perform an external validation and subsequent recalibration of the coefficients of the original variables from a prior model [11] used to predict the mortality at first admission of patients with non-reperfused ischaemic stroke.…”
Section: Designmentioning
confidence: 99%
“…The model was obtained using binary logistic regression, and the variables included were age, sex, 30-day readmission status, chronic ischaemic heart disease, diabetes mellitus, hypertension, dyslipidaemia, heart failure, and symptoms suggestive of posterior circulation stroke. More detailed information on the BM can be found in the original publication [11].…”
Section: Information Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that stroke outcomes correlate with CTI and stroke parameters computed from images. Lea-Pereira et al [ 10 ] predicted mortality risk scores during admission for ischemic stroke with CTI such as age, sex, readmission, and neurological symptoms, and an AUC of 0.742 was obtained with a logistic regression model. Ref.…”
Section: Introductionmentioning
confidence: 99%